2020
DOI: 10.7150/ijbs.42197
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetyltransferase (HAT) P300/CBP Inhibitors Induce Synthetic Lethality in PTEN-Deficient Colorectal Cancer Cells through Destabilizing AKT

Abstract: PTEN, a tumor suppressor, is found loss of function in many cancers, including colorectal cancer. To identify the synthetic lethal compounds working with PTEN deficiency, we performed a synthetic lethality drug screening with PTEN-isogenic colorectal cancer cells. From the screening, we found that PTEN -/colorectal cancer cells were sensitive to anacardic acid, a p300/CBP histone acetyltransferase (HAT) inhibitor. Anacardic acid significantly reduced the viability of PTEN -/-cells not in PTEN +/+ cells via ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…These effects have been linked to the capacity of these compounds to inhibit acetyl-transferases [ 16 , 18 , 32 , 33 ], which is a mechanism that is well characterized for 6SA. The myeloprotective effect and the protection of WBCs could be related to the previous immunomodulatory effect described for 6SA by our group and others [ 13 , 25 ], namely the ability of 6SA to induce the phosphorylation of kinases important for the proliferation of immune cells, particularly T lymphocytes and differentiated macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have been linked to the capacity of these compounds to inhibit acetyl-transferases [ 16 , 18 , 32 , 33 ], which is a mechanism that is well characterized for 6SA. The myeloprotective effect and the protection of WBCs could be related to the previous immunomodulatory effect described for 6SA by our group and others [ 13 , 25 ], namely the ability of 6SA to induce the phosphorylation of kinases important for the proliferation of immune cells, particularly T lymphocytes and differentiated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of AAs include cytotoxic, antibacterial, and antiproliferative activities [ 6 , 10 , 11 , 12 , 13 , 14 ]. The main AA found in the bark of A. adstringens is 6-pentadecyl salicylic acid (6SA) ( Figure 1 ) , which is a well-characterized histone acetyltransferase inhibitor [ 15 , 16 ] that shows cytotoxic and antiproliferative activities in different cancer cell lines [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and antineoplastic activity in xenografts in immunodeficient [ 19 , 24 ] and autologous cancer [ 25 ] models. 6SA also does not display cytotoxic effects in normal human peripheral blood mononuclear cells, in contrast to the most commonly used antineoplastic agents, which are cytotoxic to blood cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the acetylated form, E2F1 recruits P300/CBP to the site of DNA damage, causing chromatin remodelling and facilitating DNA repair [ 34 ]. Drug-resistant PTEN −/− cancer cells treated with anacardic acid (AA) showed decreased viability and increased apoptosis [ 35 ]. In this experiment, the authors also observed Heat Shock Protein 70 (HSP70) and AKT1 reduction.…”
Section: Histone Acetyltransferasesmentioning
confidence: 99%
“…HSP70 is responsible for folding and refolding misfolded proteins and for the degradation of abnormal proteins. Downregulation of P300/CBP and the reduction of HSP70 causes AKT1 reduction on a transcriptional and post-translational level in PTEN −/− prostate cancer cells [ 35 ].…”
Section: Histone Acetyltransferasesmentioning
confidence: 99%
“…It is well established that P300 plays a critical role in the DNA damage response by facilitating repair at sites of double strand breaks (DSB) through acetylation of histones and chromatin decompaction (4245). Selective inhibition of P300 HAT activity using C646 small molecule inhibitor has been shown to inhibit cell growth and sensitize cells to DNA damaging agents in other cancers including melanoma (46) NSLC (47), colorectal (48), prostrate (49,50) and neuroblastoma (51). Consistent with these studies, we found that blocking P300 HAT activity resulted in significant reduction of chromatin accessibility and H3K27ac in vascular gene regions in response to radiation.…”
Section: Discussionmentioning
confidence: 99%